Drinking Water Microbiological Studies in Relation to Human Health: Assessing the Microbiological Quality of Drinking Water in India (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Most of India is considered highly water-stressed due to the high ratio of annual waterconsumption to availability. Commonly found in India, calcium bicarbonate (Ca-HCO3) ground water hasan EC of 750 microsiemens (Scm) at 250 degrees Celsius. They are of mixed cation and mixed aniontype when the electrical conductance (EC) is between 750 to 3000 Scm, and they are of sodium chloride(Na-Cl) type when the EC is over 3000 Scm. Over 70 samples of drinking water were analyzedmicrobiologically in this study.